Factors Influencing Customers’ Adoption of Digital Wallets: A Systematic Review (Al-Farooq Journal of Sciences, 2026)
This study aimed to analyze and identify the factors influencing customers’ adoption of digital wallets through a systematic review of the relevant literature, in light of the rapid expansion of financial technology solutions and the growing transition toward a digital economy. The significance of this study stems from the increasing role of digital wallets in enhancing electronic payment systems, promoting financial inclusion, and improving the efficiency of financial transactions for individuals and organizations. The study adopted a systematic literature review approach based on the PRISMA framework, as one of the most widely recognized methodological frameworks for evidence synthesis studies. Relevant studies were retrieved from several reputable academic databases, with a primary focus on studies published between 2018 and 2025, while also incorporating selected foundational studies published earlier due to their theoretical significance. After applying the inclusion and exclusion criteria, the systematic screening process resulted in 20 studies being selected as the final sample for analysis. The findings revealed that digital wallet adoption is influenced by an integrated set of technological, behavioral, social, and security-related factors. The most prominent determinants included perceived ease of use, perceived usefulness, trust, security, social influence, facilitating conditions, demographic factors, and continuance usage. The study also showed that the success of digital wallets does not depend solely on initial adoption, but also on service providers’ ability to ensure user satisfaction, strengthen trust, and deliver a stable and secure user experience that supports long-term sustainable usage. The review further identified several research gaps, including the limited number of empirical studies conducted in Arab contexts and emerging markets, the shortage of research addressing continuance usage, and the scarcity of studies offering comprehensive explanatory models that integrate multiple determinants within a single framework. Accordingly, the study recommends developing more user-friendly and secure applications, enhancing digital financial literacy, and expanding future research focusing on developing contexts and emerging variables such as user experience, digital personalization, and artificial intelligence. This study contributes by providing a comprehensive and integrated understanding of the determinants of digital wallet adoption, thereby supporting researchers, policymakers, and financial institutions in designing more effective strategies to enhance the use of digital wallet services and maximize their economic and social impact.
Keywords: Digital wallets, Technology adoption, Electronic payment, Trust, Security, Systematic review.